A Stimulus‐Responsive Zinc–Iodine Battery with Smart Overcharge Self‐Protection Function. Issue 16 (5th March 2020) - Wang, Faxing; Tseng, Jochi; Liu, Zaichun; Zhang, Panpan; Wang, Gang; Chen, Guangbo; Wu, Weixing; Yu, Minghao; Wu, Yuping; Feng, Xinliang
Abstract: Zinc–iodine aqueous batteries (ZIABs) are highly attractive for grid‐scale energy storage due to their high theoretical capacities, environmental friendliness, and intrinsic non‐flammability. However, because of the close redox potential of Zn stripping/platting and hydrogen evolution, slight overcharge of ZIABs would induce drastic side reactions, serious safety concerns, and battery failure. A novel type of stimulus‐responsive zinc–iodine aqueous battery (SR‐ZIAB) with fast overcharge self‐protection ability is demonstrated by employing a smart pH‐responsive electrolyte. Operando spectroelectrochemical characterizations reveal that the battery failure mechanism of ZIABs during overcharge arises from the increase of electrolyte pH induced by hydrogen evolution as well as the consequent irreversible formation of insulating ZnO at anode and soluble Zn(IO3 )2 at cathode. Under overcharge conditions, the designed SR‐ZIABs can be rapidly switched off with capacity degrading to 6% of the initial capacity, thereby avoiding continuous battery damage. Importantly, SR‐ZIABs can be switched on with nearly 100% of capacity recovery by re‐adjusting the electrolyte pH. This work will inspire the development of aqueous Zn batteries with smart self‐protection ability in the overcharge state. Abstract : Integrating stimulus responses into rechargeable batteries shows potential to revolutionize energy storage for smart devices. A stimulus‐responsive Zn–I2 battery can be rapidly switched off with capacity degrading to 6% of the initial capacity under overcharge conditions, thereby preventing irreversible side reactions (including hydrogen generation and electrode degradation), battery failure, and relevant safety issues.